Factors associated with Leptospira sp infection in a large urban center in northeastern Brazil Fatores associados à infecção por Leptospira sp em um grande centro urbano do Nordeste do Brasil - Juarez Pereira Dias; Maria Glória Teixeira; Maria Conceição Nascimento Costa; Carlos Maurício Cardeal Mendes; Patrícia Guimarães; Mitermayer Galvão Reis; Albert Ko; Maurício Lima Barreto (Revista da Sociedade Brasileira de Medicina Tropical, 2007)
Leptospirosis is a zoonotic disease that has emerged to cause epidemics in urban communities in developing countries. However, little is known about the infection in the general population. A seroprevalence survey was performed on a random sample of 1,390 subjects in Salvador, Brazil. Data on environmental and socioeconomic factors were collected. The microagglutination test of serum samples was used to show any prior Leptospira infection. The overall seroprevalence was 12.4%. Among the seropositive individuals, 111 (61%) had high titers for serovars of the Icterohaemorrhagiae serogroup. Seroprevalence increased with age and was similar for males and females. A positive correlation between Leptospira infection and low educational level was found. These findings indicate that a significant proportion of this urban population is exposed to pathogenic Leptospira. Public health actions for leptospirosis control will need to target not only the traditional groups at risk of infection with severe forms of this disease, but also the general population that is at risk. A leptospirose é uma zoonose que tem emergido causando epidemias em comunidades urbanas de países em desenvolvimento. Entretanto, pouco é conhecido sobre infecção na população geral. Inquérito de soroprevalência foi realizado em amostra randômica de 1.390 indivíduos de Salvador, Brasil. Dados sobre fatores ambientais e sócio-econômicos foram coletados. Teste de Microaglutinação de amostras de soro foi utilizado para evidenciar infecção anterior por Leptospira. Soroprevalência global foi 12,4%. Entre os soropositivos, 111 (61%) tinham altos títulos para os sorovares do serogrupo Icterohaemorrhagiae. A soroprevalência aumentou com a idade e foi similar entre homens e mulheres. Encontrou-se correlação positiva entre infecção por Leptospira e baixo nível educacional. Os achados indicam que significativa proporção dessa população urbana está exposta a Leptospira patogênica. Ações de saúde pública para controle desta doença necessitarão ter como alvo não só os ...